2019
DOI: 10.1021/acs.joc.9b01972
|View full text |Cite
|
Sign up to set email alerts
|

Imidate as the Intact Directing Group for the Cobalt-Catalyzed C–H Allylation

Abstract: Cobalt-catalyzed C−H allylation reactions of NHfree benzimidates using vinylcyclopropanes or allyl carbonate are reported. The reactive and relatively unstable imidate groups remain intact during the C−H allylations to afford functionalized imidates without dealcoholizations. The thus obtained allylated imidate was subsequently converted into other heterocyclic structures through a following C−H functionalization reaction, demonstrating the synthetic utility of this method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 72 publications
0
21
0
Order By: Relevance
“…[7][8][9][10] In contrast, the catalytic activity of Cp*Co(III) complexes has long been ignored and remained mostly unexplored until recently. The recent upsurge of publications dealing with the use of Cp*Co(III)-catalysts in C-H bond functionalizations [11][12][13][14][15][16] was triggered by the remarkable reports by Kanai and Matsunaga [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] (scheme 1) and by Ackerman et al [34][35][36][37][38][39][40][41][42][43][44][45] and followed by a number of other reports. 46,47 In many reported cases this powerful class of cobalt catalysts 11 presents reactivity profiles that differ from their rhodium and iridium analogues.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[7][8][9][10] In contrast, the catalytic activity of Cp*Co(III) complexes has long been ignored and remained mostly unexplored until recently. The recent upsurge of publications dealing with the use of Cp*Co(III)-catalysts in C-H bond functionalizations [11][12][13][14][15][16] was triggered by the remarkable reports by Kanai and Matsunaga [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] (scheme 1) and by Ackerman et al [34][35][36][37][38][39][40][41][42][43][44][45] and followed by a number of other reports. 46,47 In many reported cases this powerful class of cobalt catalysts 11 presents reactivity profiles that differ from their rhodium and iridium analogues.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to mention that known syntheses (scheme 1) of Cp*Co(III)-metallacycles are based on the use of sensitive Cp*Co(I)L2 (L=CO; Me3SiCH=CH2) complexes and rely on an oxidative addition step requiring expensive iodo-arene substrates such as 2-(2-iodophenyl)pyridine (oxidative addition). 53 A variant operating via electrophilic metallation inspired from the early applications to catalysis of Matsunaga and Kanai [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]48 makes use of [Cp*Co(III)(MeCN)3](BF4)2 56 and excess of 2-phenylpyridine, i.e 2-phpyH (scheme 1c). Another one proposed by Zhu et al 16,54 with Cp*Co(CO)I2 requires 2 eq of silver acetate to promote the formation of cobaltacycles (scheme 1d) with no evidence of the dominance of the CMD mechanism.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Functionalization of various groups via imidate formation is well known, and they are the important class of intermediates to introduce different groups, 29 as well as acting as a directing group. 30 Different imidate-based complexes of gold 31 and palladium 32 are also known for use in catalysis. Among which, trichloroacetimidates are known to be powerful leaving groups in glycoscience [33][34][35][36] and have been extensively explored as glycosyl donors in glycosylation reactions with various acceptors in the presence of a suitable promoter.…”
Section: Paper Synopenmentioning
confidence: 99%
“…For example, early reports have demonstrated that VCPs were compatible coupling partners, merging C-H/C-C activations with the aid of transition-metal catalysts to provide the allylated products. [30][31][32][33][34] The use of cyclopropanols as useful building blocks for the synthesis of β-aryl ketones via Rh(III)catalyzed alkylation of (hetero)arenes has also been achieved. 35,36 However, these pioneering works were confined to the use of Mn, 32 Ru, 33 Rh, 30,[35][36][37][38][39] and Co 31,40 catalysts and generally proceeded by C-H/C-C bond cleavage occurring within the same catalytic cycle.…”
Section: Introductionmentioning
confidence: 99%